White‐Light‐Emitting Materials Constructed from Supramolecular Approaches. Issue 20 (29th July 2018) - Li, Dengfeng; Wang, Jie; Ma, Xiang
Abstract: White‐light emissive materials are gaining increasing attentions, ascribed to the potential applications in display and lighting devices as well as sensors. The realization of white‐light emission demands either the simultaneous emission of red, green, and blue colors or at least two complementary colors with similar distribution of emission intensities covering the entire visible spectrum. The introduction of supramolecular approaches not only relieves the negative effects of intermolecular interactions and energy transfer processes, but also endows the white‐light emissive materials with the capacity of color tunability and stimuli‐responsiveness, due to the dynamic and reversible nature of noncovalent interactions. Supramolecular materials with well‐ordered structures can regulate the energy transfer by the assembly–disassembly process, and meanwhile bring in extra fascinating attributes. This review mainly describes the recent reports on fabricating white‐light‐emitting materials from supramolecular approaches such as hydrogen bonding, host–guest interaction, π–π stacking, and metal coordination, which enriches the conceptions and pathways to afford such materials. Moreover, some perspectives together with pressing challenges are presented in the end, synchronously forecasting the potential trends of white‐light emissive materials. Abstract : This review summarizes the recent reports on fabricating white‐light‐emitting materials from supramolecular approaches such as hydrogen bonding, host–guest interaction, π–π stacking, and metal coordination, which enriches the concepts and pathways to enable such materials. Moreover, some perspectives together with pressing challenges are presented in the end, synchronously forecasting the potential trends of white‐light emissive materials.